A MULTI‐CENTRE, RANDOMISED TRIAL TO ASSESS WHETHER INCREASED DIETARY FIBRE INTAKE (USING A FIBRE SUPPLEMENT OR HIGH‐FIBRE FOODS) PRODUCES HEALTHY BOWEL PERFORMANCE AND REDUCES LAXATIVE REQUIREMENT IN FREE LIVING PATIENTS ON PERITONEAL DIALYSIS. Issue 3 (20th March 2014) - Sutton, Debbie; Ovington, Susan; Engel, Barbara
SUMMARY Background Constipation is a significant problem for many patients on peritoneal dialysis (PD). Due in part to dietary restrictions it is a common cause of technique failure and poor dialysis efficacy. Both consequences have an economic cost as well as contributing to a poor patient experience. Objective This study aimed to investigate whether an appropriate daily bowel habit could be achieved through a higher fibre intake, minimal use of laxatives and with no adverse effect on potassium, phosphate and fluid balance. Methods One hundred and seven patients who had been on PD for at least three months were recruited from seven renal units. They were asked to record daily bowel habits (Bristol Stool Form Scale: BSFS) and laxative use for four weeks. From this group 41 suitable patients with regular laxative use were identified and invited to enter the Intervention stage, Stage 2. Patients were randomised into one of three intervention arms: high fibre supplement (HFS); high fibre diet (HFD) or placebo. Results During the intervention stage, intake of HFS increased significantly between week 1 and week 4 (p = 0.04) and in the placebo group between week 1 and week 3 (p = 0.02). There was no significant increase in fibre intake for those on the HFD. Laxative dose appeared to decrease in the HFS group (38%) and the HFD group (16%) but these changes were not significant when compared to the placebo. Conclusion This study has confirmed the prevalence of laxative use amongst patients on PD and shown that fibre use can confer improvements in bowel function without affecting biochemistry.